2021
DOI: 10.1101/2021.03.26.437167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A distinct brain expression profile for genes within large introgression deserts and under positive selection inHomo sapiens

Abstract: Analyses of ancient DNA from extinct hominins have provided unique insights into the complex evolutionary history of Homo sapiens, intricately related to that of the Neanderthals and the Denisovans as revealed by several instances of admixture events. These analyses have also allowed the identification of introgression deserts: genomic regions in our species that are depleted of `archaic' haplotypes. The presence of genes like FOXP2 in these deserts has been taken to be suggestive of brain-related functional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In that context our a-cTF candidate JUN is interesting, as the enrichment results for this TF are based on diverse TF target prediction algorithms that employ diverse methods, including computational prediction based on binding motifs, manual curation from individual experimental tests and experimental data such as ChipSeq experiments. The observation that both a-cTFs are brain cis-eQTL is noteworthy in the context of previous work that has shown that archaic deserts are enriched for brain genes ( Vernot et al 2016 ; Buisan et al . 2021 ) and the cis-eQTL aSNPs show signals of positive selection.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In that context our a-cTF candidate JUN is interesting, as the enrichment results for this TF are based on diverse TF target prediction algorithms that employ diverse methods, including computational prediction based on binding motifs, manual curation from individual experimental tests and experimental data such as ChipSeq experiments. The observation that both a-cTFs are brain cis-eQTL is noteworthy in the context of previous work that has shown that archaic deserts are enriched for brain genes ( Vernot et al 2016 ; Buisan et al . 2021 ) and the cis-eQTL aSNPs show signals of positive selection.…”
Section: Discussionmentioning
confidence: 51%
“…Notably, JUN was one of two a-cTFs ( PRDM5 ) with predicted target genes being enriched in genomic regions devoid of Neandertal and Denisovan DNA. These regions have previously been suggested to be a result of negative selection against introgressed DNA and have been shown to be enriched for brain-related genes and depleted of testes expressed genes ( Sankararaman et al 2016 ; Vernot et al 2016 ; Buisan et al . 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, JUN was one of two a-cTFs ( PRDM5 ) with predicted target genes being enriched in genomic regions devoid of Neandertal and Denisovan DNA. These regions have previously been suggested to be a result of negative selection against introgressed DNA and have been shown to be enriched for brain-related genes and depleted of testes expressed genes (Buisan et al, 2021; Sankararaman et al, 2016; Vernot et al, 2016). Our results suggest that these regions are not out of regulatory reach for Neandertal DNA and that in fact some TFs that show cis-eQTLs with Neandertal DNA particulary target genes in these regions.…”
Section: Discussionmentioning
confidence: 99%